Ln(x+7)=(3x-5)

Simple and best practice solution for Ln(x+7)=(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(x+7)=(3x-5) equation:


Simplifying
Ln(x + 7) = (3x + -5)

Reorder the terms:
nL(7 + x) = (3x + -5)
(7 * nL + x * nL) = (3x + -5)
(7nL + nxL) = (3x + -5)

Reorder the terms:
7nL + nxL = (-5 + 3x)

Remove parenthesis around (-5 + 3x)
7nL + nxL = -5 + 3x

Solving
7nL + nxL = -5 + 3x

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Reorder the terms:
5 + 7nL + nxL + -3x = -5 + 3x + 5 + -3x

Reorder the terms:
5 + 7nL + nxL + -3x = -5 + 5 + 3x + -3x

Combine like terms: -5 + 5 = 0
5 + 7nL + nxL + -3x = 0 + 3x + -3x
5 + 7nL + nxL + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
5 + 7nL + nxL + -3x = 0

The solution to this equation could not be determined.

See similar equations:

| 6x+49=28x+9 | | 2(3x+4)+5x=-1 | | 9k-1=15 | | Ln(x+7)=ln(3x-5) | | (9y-2)(3y+5)= | | Log(7x)=3.5 | | E*-3x=7.1 | | 3t-4=4t+16 | | 3x+31=12x-559 | | 17y=3x-19 | | (9+9)=(8-8) | | 10x-63=11 | | 8x^2-9x+k=0 | | 7x-2x-3x+2.73=4.49 | | 3x-5=-41 | | 9p-7= | | z^2+56x-1920=0 | | 7x+12y=12 | | z/-4=11-5 | | 0.7x+0.5=0.9x-1.1 | | 5x-6y=19fory | | 6(3+4x)-8=202 | | 4z/10-1=-8 | | 28-4*X=8 | | 3(4-2n)=2(7-n) | | 0.5/6=120/x | | 5x=12+2y | | 5/x=6/684 | | 3x+5x=150 | | 9-(2y-8)=6-3y | | 10m-26=4 | | -16(0)+128(0)+1680= |

Equations solver categories